You need to notice that the problem provides the information that `ln x> 2(x-1)/(x+1), ` hence `ln x -2(x-1)/(x+1) > 0` .

Notice that the expression `ln x - 2(x-1)/(x+1)` represents the equation of the function f(x) such that:

`f(x) > 0`

The inequality `f(x) > 0 ` tells that the function...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to notice that the problem provides the information that `ln x> 2(x-1)/(x+1), ` hence `ln x -2(x-1)/(x+1) > 0` .

Notice that the expression `ln x - 2(x-1)/(x+1)` represents the equation of the function f(x) such that:

`f(x) > 0`

The inequality `f(x) > 0 ` tells that the function has the minimum value equal to 0, hence, you need to solve for x the following equation, such that:

`ln x - 2(x-1)/(x+1) = 0`

Notice that for `x = 1` , the equation is checked, such that:

`ln 1 - 2(1-1)/(1+1) = 0 => 0 - 2*0/2 = 0 => 0 - 0 = 0 => 0 = 0`

**Since the function reaches its minimum at `x = 1` , hence, the inequality holds for `x in (1,oo).` **